2010
DOI: 10.1007/s00216-010-3947-6
|View full text |Cite
|
Sign up to set email alerts
|

Solid-phase extraction liquid chromatography–tandem mass spectrometry analytical method for the determination of 2-hydroxy-4-methoxybenzophenone and its metabolites in both human urine and semen

Abstract: 2-Hydroxy-4-methoxybenzophenone (HMB), which is one of the most commonly used UV filters in sunscreen cosmetics to protect skin from the deleterious effects of the sun, can be percutaneously absorbed, further metabolized, and finally excreted or bioaccumulated. An analytical method for the sensitive determination of HMB and its three metabolites in both human urine and semen is developed. The presented analytical method is based on a solid-phase extraction (SPE) procedure to clean-up and preconcentrate the tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(29 citation statements)
references
References 30 publications
1
28
0
Order By: Relevance
“…We are aware of one previous paper reporting that BP-3 can be detected and quantified in semen (37). In our previous paper focusing on these same five BP-type UV filters as measured in both partners of the couples participating in the LIFE Study, we found that male partners’ BP-2 concentrations were associated with a significant 31% reduction in couple fecundity resulting in a longer time-to-pregnancy even after adjusting for the female partners concentrations (18).…”
Section: Discussionmentioning
confidence: 99%
“…We are aware of one previous paper reporting that BP-3 can be detected and quantified in semen (37). In our previous paper focusing on these same five BP-type UV filters as measured in both partners of the couples participating in the LIFE Study, we found that male partners’ BP-2 concentrations were associated with a significant 31% reduction in couple fecundity resulting in a longer time-to-pregnancy even after adjusting for the female partners concentrations (18).…”
Section: Discussionmentioning
confidence: 99%
“…Secondary pathways would be aromatic hydroxylations carried out by the cytochrome P450 leading to the hydroxylatedmetabolites THB and DHMB [59]. Nevertheless, the predominant metabolites in human urine and semen samples during the first 24 h after topic application are the glucuronide conjugates of BP3 and BP1 [63]. None of those compounds, except BP1, were found in the fungal culture.…”
Section: Degradation Pathwaysmentioning
confidence: 95%
“…The mobile phases comprise methanol, acetonitrile and water. Besides, solvent modifiers {e.g., ammonium acetate (proton acceptor) [48], formic acid [18] and acetic acid (proton donors) [34]} are added to enhance ionization efficiencies of the target compounds.…”
Section: Determination Strategiesmentioning
confidence: 99%
“…Although some conventional bonded silica sorbents are still in use [18], these are being replaced by hydrophilic-hydrophobic balance polymeric material {e.g., Oasis HLB [36] or Strata XL [43]}. For polar anionic compounds (e.g., OPFRs and PFCs), weak-anion exchange sorbents {e.g., StrataX-AW and Oasis WAX [105]} have proved useful [25].…”
Section: Extraction and Clean-up Strategiesmentioning
confidence: 99%
See 1 more Smart Citation